1987
DOI: 10.1128/jcm.25.10.1999-2000.1987
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Clostridium difficile toxin in various tissue culture monolayers

Abstract: Thirty stool filtrates known to contain Clostridium difficile toxin based on previous testing on McCoy cells were tested for toxicity on primary African green monkey kidney (AGMK), McCoy, MRC-5, primary rhesus monkey kidney (RMK), and Vero cells. All 30 filtrates showed cytotoxic effect at-1:100 dilution on McCoy and Vero cells. A total of 22 filtrates were positive on MRC-5 monolayers, while only 16 and 10 filtrates showed positive cytotoxic effect on AGMK and RMK cells, respectively. Another 630 stool specim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…The cytotoxicity test and toxigenic culture remained the most sensitive (>92%) and specific (>99%) methods. Nevertheless, the results of the cytotoxicity assay depend, to some extent, on the cell line, the age of the cells, the way in which stool specimens are processed, and the test format; moreover, they can sometimes be limited by interfering substances in the stool specimens (21,28).…”
Section: Discussionmentioning
confidence: 99%
“…The cytotoxicity test and toxigenic culture remained the most sensitive (>92%) and specific (>99%) methods. Nevertheless, the results of the cytotoxicity assay depend, to some extent, on the cell line, the age of the cells, the way in which stool specimens are processed, and the test format; moreover, they can sometimes be limited by interfering substances in the stool specimens (21,28).…”
Section: Discussionmentioning
confidence: 99%
“…False-negative tests may reflect undetectable quantities of cytotoxin in patients with early and mild disease, the production of toxins not identified by the assay, inactivation of toxin during transport, 32 and decreased toxin sensitivity of certain cell lines. 33 Positive tests in the absence of disease may occur in up to 5% of healthy adults and hospital control patients. 25,34 The predictive models in this study showed limited ability to discriminate positive from negative outcomes (as indicated by ROC curve areas in the 0.6-0.7 range).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, our sensitivity of 80% was comparable to previously reported rates . Many factors including final dilution of inoculum, age and type of the cell line employed influence CTA results (23)(24)(25). As we batched our specimens and the cell cultures were fresh , it is doubtful that the res ults of CTA could be duplicated in the routine laboratmy setting.…”
Section: Discussionmentioning
confidence: 99%